Quality Evaluation Of Some Softening Agents Used In The South East, Nigeria - OLY-ALAWUBA, NKEIRUKA; Okechukwu-Ezike, Ngozika C. (Archives of Business Research, 2020)
Mineral composition and the Sensory attributes of Some food softening agents: Potash, dry Plantain leaf, Unripe Plantain peel, dry Palm bunch (Extracts) and their effects on African bread fruit were evaluated. The results showed the following mineral contents of the samples: Phosphorus - 15.66mg/100g (Potash) to 26.22mg/100g (Palm bunch); Iron - 2.78ppm (Palm bunch) to 6.77mg/100g (Plantain peel); Zinc contents of the samples ranged from 2.25ppm (Plantain peel) to 3.34ppm(Potash); Potassium content of the samples ranged from 27.81mg/100g (Palm bunch) to 176mg/100g(Potash); Sodium content ranged from 9.17mg/100g (Palm bunch) to 24.78mg/100g (Potash); Magnesium ranged from 11.86mg/100g (Plantain peel) to 13.44mg/100g (Potash, Plantain leaf); Lead ranged from 0.17mg/100g (Palm bunch) to 0.39mg/100g (Potash).Calcium content of the softening agents ranged from 14.69mg/100g (Palm bunch) to 27.82mg/100g (Potash). Sensory parameters of the samples evaluated were taste, colour, aroma, texture and general acceptability. The mean taste scores of the samples ranged from 4.44 (Palm bunch extract) to 6.72 (Potash), mean colour scores ranged from 4.04 (Palm bunch extract) to 6.44 (Potash extract), mean aroma scores ranged from 4.04 (Palm bunch extract) to 6.08 (Plantain peel). Texture of the samples ranged from 8.1 (Plantain peel, Plantain leaf extracts) to 8.4 (Palm bunch extract). The general acceptability of the samples ranged from 7.20 (Palm bunch, Potash extracts) to 7.5, (plantain peels extracts).The plantain peel extract had the highest mean sensory scores in terms of overall acceptability. Its effects as a softening agent were similar to those of the potash which served as a control sample.